STUDYING THE STRUCTURAL BEHAVIOR OF BRICK WALLS STRENGTHENED BY DAMAGED TIRES STRIPS - Yamama Alaasam; Ahmed Alalikhan (Mağallaẗ Al-kūfaẗ Al-handasiyyaẗ)
The present study involves strengthening process applied upon brick walls to increase their ultimate load carrying capacity or improving their ductility behavior by using different types of strengthening materials. These materials include either traditional well-known materials or newly proposed materials. The traditional materials include steel wire mesh (SWM) and carbon fiber-reinforced polymer sheet (CFRPS) while the proposed materials include recycled damaged tire strips (DTS). The purpose of using such abundant and polluted material is to satisfy, respectively, the economic considerations and clean environment in the field of enhancing the structural behavior of brick walls. Eight brick walls models were constructed with dimensions of (1200×1200×240) mm, respectively represent width, height and thickness of each model to be tested by 45° compressive loading. Results exhibited that, the SWM increases the ultimate load carrying capacity for the strengthened models to 51.85% compared to the non-strengthened model when placed on one side of the model. Also, the use of CFRPS placed on one side and on both sides of the strengthened models increases the ultimate load capacity respectively to 18.2% and 385% compared to the non-strengthened model. The DTS material has no ability to increase the ultimate load capacity (-18.2 %) but it successfully converts the brittle behavior of the brick walls to a ductile one. It is recommended to use DTS to increase the ductility for brick walls that are likely be damaged or collapsed to avoid the sudden failure.